Molecular Genetic Assessment Aids in Clarifying Phylogenetic Status of Iranian Kerman Wild Sheep - Arsen V. Dotsev; Mohammad Hossein Moradi; Tatiana E. Deniskova; Ali Esmailizadeh; Neckruz F. Bakoev; Olga A. Koshkina; Darren K. Griffin; Michael N. Romanov; Natalia A. Zinovieva (Animals)
Two species of wild sheep inhabit Iran: Asiatic mouflon (Ovis gmelini) and urial (O. vignei). Phylogenetic relationships between populations distributed in this country are complex and still remain unclear. This study aimed to clarify, by genetic assessment, the phylogenetic status of Kerman wild sheep, considered to be a hybrid of the two species. For this purpose, we created a dataset that included specimens of O. gmelini, O. vignei, and Kerman sheep. We applied genome-wide SNP genotyping technology to analyze population structure and genetic diversity of these groups. Using Neighbor-Net and PCA plots, it was demonstrated that Kerman sheep were differentiated from other groups and occupy an intermediate position between O. gmelini and O. vignei. Using Admixture analysis, two ancestral components were identified in this population; however, admixed ancestry was not confirmed by f3 statistics. Genetic diversity in Kerman wild sheep was significantly higher than in any group of O. vignei, but lower than in O. gmelini. Additionally, we examined complete mitochondrial genomes and it was demonstrated that the matrilineal ancestor of Kerman sheep belonged to O. vignei. Our results lead to the conclusion that Kerman wild sheep can be recognized as a separate subspecies of O. vignei.